Graft preservation confers myocardial protection during coronary artery bypass grafting - Szalkiewicz, Philipp; Emmert, Maximilian Y.; Heinisch, Paul P.; Arnold, Zsuzsanna; Crailsheim, Ingo; Mach, Markus; Aschacher, Thomas; Grabenwöger, Martin; Winkler, Bernhard (Frontiers in Cardiovascular Medicine, 2022)
Background During on-pump coronary artery bypass grafting (ONCAB), graft flushing for distal anastomoses testing also perfuses the downstream myocardium. This single-center retrospective study evaluated the impact of specific preservation solutions on myocardial protection during ONCAB. Materials and methods Between July 2019 and March 2020 either DuraGraft (DG) or 0.9% Saline/Biseko (SB) was applied to 272 ONCAB. Overall, 166 patients were propensity-matched into two groups. Cardiac enzymes [high-sensitive Troponin I (hs-TnI) and creatine kinase (CK)] were evaluated 7 days post-surgery. Results Post-surgery, hs-TnI values were significantly lower from 3 to 6 h (h) up to 4 days in the DG group: 3–6 h: 4,034 ng/L [IQR 1,853–8,654] vs. 5,532 ng/L [IQR 3,633—8,862], p = 0.05; 12–24 h: 2,420 ng/L [IQR 1,408–5,782] vs. 4,166 [IQR 2,052–8,624], p < 0.01; 2 days: 1,095 ng/L [IQR 479–2,311] vs. 1,564 ng/L [IQR 659–5,057], p = 0.02 and at 4 days: 488 ng/L [IQR 232–1,061] vs. 745 ng/L [IQR 319–1,820], p = 0.03. The maximum value: 4,151 ng/L [IQR 2,056–8,621] vs. 6,349 ng/L [IQR 4,061–12,664], p < 0.01 and the median area under the curve (AUC): 6,146 ng/L/24 h [IQR 3,121–13,248] vs. 10,735 ng/L/24 h [IQR 4,859–21,484], p = 0.02 were lower in the DG group. CK values were not significantly different between groups: maximum value 690 [IQR 417–947] vs. 631 [464–979], p = 0.61 and AUC 1,986 [1,226–2,899] vs. 2,081 [1,311–3,063], p = 0.37. Conclusion Repeated graft flushing with DG resulted in lower Troponin values post-surgery suggesting enhanced myocardial protection compared to SB. Additional studies are warranted to further assess the myocardial protection properties of DG.